KEANEKARAGAMAN TUMBUHAN PAKU (Pteridophyta) DI KAWASAN WISATA JOBEN DESA PESANGERAHAN KECAMATAN MONTONG GADING KABUPATEN LOMBOK TIMUR - Asri, Indra Himayatul; Marzuki, M (Cocos Bio, 2020)
The purpose of this research is to know the diversity of nail plants   (Pteridophyta)   in   Tourism   Joben   area   Pesanggrahan Village, Montong Gading Subdistrict, East Lombok regency. The type of this research is descriptive explorative. The instrument used is to use an observation sheet in the form of tables, which serve as a place to record the results of observations on each treatment under study. Data analysis conducted descriptively by counting are: 1) Index of species diversity, 2) Index of type dominance. Based on the results of the research, nail plants found in Joben  there  are  6  types  of  Microsorum  grossum,  Asplenium nidus, Mikrolepia speluncae, Depasta petersenii, Davalia solida and Asplenium tenerum. While the mean index of the diversity of fern-plant species found in the Joben area in the observation plot (quadrant I-V) was H = 0.9386. This diversity index belongs to the low category [H '= <1,0]. And the dominant index of the average type of fern plants from the observation plot (quadrant I- V) of 0.446 this dominant index of the fern-plant species belongs to  the  low  category  C  =  <0.50).  We  can  conclude  that  the diversity of nail-fern plants in the area of Joben Tourism is of low diversity and the absence of dominant species